22q11.2 microduplication syndrome and juvenile glaucoma. (4th July 2018) - Di Matteo, Federico; Bettin, Paolo; Ferrari, Giulia; Fiori, Marina; Ciampi, Carlo; Manfredini, Emanuela; Rabiolo, Alessandro; Bandello, Francesco
ABSTRACT: Background : 22q11.2 microduplication is a relatively recently recognized syndrome. Findings in affected individuals range from apparent normality to a wide variety of systemic and ocular conditions. We describe the association between 22q11.2 microduplication and juvenile glaucoma in two brothers. Materials and Methods : We reviewed ophthalmological, genetic, and hematological medical records of two patients and their unaffected mother. Results : A 2.07 Mb interstitial duplication in 22q11.21 and a smaller 182 kb duplication in 22q11.23 were identified in both subjects. Patient 1 showed an initial intraocular pressure (IOP) of 15 mmHg in right eye (RE) and 32 mmHg in left eye (LE) under maximum medical treatment. Deep sclerectomy surgery in LE was converted to trabeculectomy due to a macroperforation of the trabeculo-descemetic membrane. Postoperatively, the patient developed persistent hypotony with retinal folds, while IOP in RE increased to 28 mmHg. Trabeculectomy in RE was also complicated by persistent hypotony. Autologous blood injection was performed, resulting in an increase in both visual acuity and IOP. Patient 2 presented with an IOP of 29 mmHg in RE and 33 mmHg in LE. We planned an elective trabeculectomy and added orally administered acetazolamide. The patient developed bilinear cytopenia that contraindicated the surgical procedure. After hematologic normalization, the patient underwent trabeculectomy in LE, causing persistent hypotony. We performed deep sclerectomy surgery in RE, without any significant intra- or post-operative complications. Conclusions : 22q11.2 microduplication syndrome can be associated with juvenile glaucoma. Trabeculectomy may be complicated by persistent hypotony. Deep sclerectomy appears to be a better surgical option, although the presence of a thin sclera may result in conversion to trabeculectomy.